Trends in Educational Attainment and Field of Study Among Adults in the European Union - NICA, Elvira; DIMA, Cristina; DUMITRESCU, Oana Cătălina; ANGHELUȚĂ, Petrică Sorin (European Journal of Sustainable Development, 2025)
Given the evolution of the labor market, adult participation in vocational education and training programs is becoming increasingly important. For the period 2013-2023, the article presents the comparative situation of this indicator. The values for both employed and unemployed people are analyzed. Thus, the level and type of skills held by people are influenced. Technological changes lead to the need for many people to update their skills. Jobs that require low levels of education are increasingly rare. For communities where the level of education of people has increased, an increase in productivity has also been observed. Completing a higher level of education offers a superior possibility of finding a safer and better-paid job. A higher share of people with a tertiary education level creates premises for the development of a community. The article presents the analysis of the evolution of the share of the adult population with tertiary education attainment. The degree of employment on the labor market can also be influenced by the fields of education. Thus, the fields of education of bachelor's, master's and doctoral graduates are analyzed. Keywords: graduates, bachelor, master, doctoral, participation rate in education and training, European Union